Faculty Perceptions of Online Teaching at a Mid-Sized Liberal Arts University - Shreaves, Dana L; Ching, Yu-Hui; Uribe-Florez, Lida; Trespalacios, Jesús (Online Learning, 2020)
This mixed-methods study examined faculty perceptions of online teaching at a mid-sized liberal arts university in order to understand faculty acceptance and participation in online teaching at the university. Seventy-nine participants responded to a survey that collected qualitative and quantitative data. Content analysis examined faculty perceptions of online teaching and identified six themes. An examination of 21 quantitative factors identified 17 factors reported by more than 50% of respondents to influence their decision to teach or not teach online. Study participants perceived online learning as attractive to students but they wanted any online courses carefully regulated, in part because online learning was seen as contrary to their teaching values. Participants were influenced by personal preferences but also the desire for robust faculty resources, and more effective technology and infrastructure. Implications and directions for future research were discussed.